Sepsis in Pregnancy and Postpartum. Issue 5 (September 2019) - Simpson, Kathleen Rice
Abstract : Sepsis in pregnancy and postpartum is a major cause of maternal death in the United States. As part of the continuing focus on preventing maternal mortality, new resources are reviewed, including the Society for Maternal-Fetal Medicine Consult Series on sepsis during pregnancy and the puerperium. Working together as part of an interdisciplinary team requires that all members of the team have knowledge of the most recent clinical guidelines and the ability to apply them to clinical practice.